Photo of fish flake in New Bonaventure - Millar, Edward (2012)
Fish flake in New Bonaventure; behind Bruce Miller's stage; boughs on top of wooden frame; lobster pot in foreground on flake Boughs would be placed onto the flakes to prevent the cod from sticking to the wood when drying. Chicken wire has become commonly used in substitute of boughs.